On the operon structure of the nitrogenase genes of Rhizobium leguminosarum and Azotobacter vinelandii. - Krol, A J (1982)
The transcription of the nitrogenase genes in Rhizobium leguminosarum was studied by analysing total cellular RNA from bacteroids for the presence of nitrogenase messenger RNA. The RNA was separated by agarose gel electrophoresis and blotted onto nitrocellulose filters. Messenger RNA for nitrogenase was detected by hybridization with probes derived from plasmid pSA30, a recombinant plasmid carrying the nitrogenase genes of Klebsiella pneumoniae. In the same way nitrogenase mRNA was detected in RNA isolated from Azotobacter vinelandii and from Klebsiella pneumoniae, but only if both were cultured under conditions of derepression of the nitrogenase genes. The size of the RNA hybridizing with the probes indicates that in all three organisms the genes for the subunits of the two components of nitrogenase constitute a single operon.